Proximate, Mineral and Phytate Profiles of Some Selected Spices Found in Nigeria (Biological Sciences - PJSIR, 2005)
. The proximate, mineral and phytate (phy) compositions, as well as the calculations for fatty acid, metabolisable energy, phy:Zn, Ca:phy and [Ca] [phy]/[Zn] were determined in 13 spices (S11 - S23) used as seasoning agents in Nigeria. The mean values of various parameters for proximate composition (g/100 g) were: moisture (3.61±3.56), dry matter (96.39±3.56), crude fat (5.46±10.02), crude fibre (27.0±17.34), crude protein (13.78±9.84), ash (4.57±2.22) and carbo- hydrates (45.58±22.25). Fatty acids were noted to be 4.37±8.02 (g/100 g) and energy was 1211.23±317.64 (kJ/100 g). Significant differences (P < 0.05) existed in moisture, dry matter, fat, fibre, crude protein and fatty acid levels. Minerals (mg/100  g)  included:  Na  (183.08±144.19),  K  (1621.54±1703.99),  Ca  (505.38±463.24),  Mg  (243.08±235.74), Zn(434.92±945.86), Fe (72.54±92.38) and P (740±624.64), while Pb, Cu and Co, were not detected. The relationships between Na and K as well as between Ca and P were mostly within the desirable range with the respective ratios of Na/K (0.59±0.87) and Ca/P (2.20±3.32). Significant differences existed among the levels of Na, K, Ca, Mg, Zn, Fe, Na/K and Ca/P. The [Ca] [phy]/[Zn] had an overall mean value of 1.45±1.74 showing that the bioavailability of zinc in the spices may be low (except in S21, S22  and S23) due to the high phytate content of the spices.